2012
DOI: 10.1073/pnas.1114153109
|View full text |Cite
|
Sign up to set email alerts
|

CC chemokine receptor 4 is required for experimental autoimmune encephalomyelitis by regulating GM-CSF and IL-23 production in dendritic cells

Abstract: Dendritic cells (DCs) are pivotal for the development of experimental autoimmune encephalomyelitis (EAE). However, the mechanisms by which they control disease remain to be determined. This study demonstrates that expression of CC chemokine receptor 4 (CCR4) by DCs is required for EAE induction. CCR4 −/− mice presented enhanced resistance to EAE associated with a reduction in IL-23 and GM-CSF expression in the CNS. Restoring CCR4 on myeloid cells in bone marrow chimeras or intracerebral microinjection of CCR4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 44 publications
2
65
0
Order By: Relevance
“…We demonstrated before that the CCL17/CCR4 axis affects the function of CCR4 ϩ myeloid cells, but not T lymphocytes, recruited into the brain during CNS autoimmunity (64). It is thus possible that CCL17 favors brain recruitment or function of myeloid cells rather than CD8…”
Section: Flammatory Cytokines Were Detected In Infected Cnr2mentioning
confidence: 99%
“…We demonstrated before that the CCL17/CCR4 axis affects the function of CCR4 ϩ myeloid cells, but not T lymphocytes, recruited into the brain during CNS autoimmunity (64). It is thus possible that CCL17 favors brain recruitment or function of myeloid cells rather than CD8…”
Section: Flammatory Cytokines Were Detected In Infected Cnr2mentioning
confidence: 99%
“…At the level of transcriptional profiling this has been indicated by direct comparison of defined DC subsets from different lymphoid organs [11]. We have shown that the inflammatory chemokine CCL17, a ligand of CCR4, marks a population of CD8α [18,19], and participate in cytokine-dependent Th17 differentiation [20].…”
Section: Introductionmentioning
confidence: 99%
“…At the level of transcriptional profiling this has been indicated by direct comparison of defined DC subsets from different lymphoid organs [11]. We have shown that the inflammatory chemokine CCL17, a ligand of CCR4, marks a population of CD8α [18,19], and participate in cytokine-dependent Th17 differentiation [20].In the present study, we intended to identify the molecular factors, which regulate CCL17 expression in resident CD8 − CD11b + DCs of the spleen as compared to the corresponding LN DCs. Based on characteristic differences in genome-wide expression profiling, we show that suppression of CCL17 production in the spleen is mediated through IFN-γ and that LN DCs can escape from this suppression by downregulation of the IFN-γR.…”
mentioning
confidence: 99%
“…Thus, they give a warning on rapid translational studies. The most important aspect of our study was the finding that dendritic cells (DCs) are the relevant cellular subset mediating CCR4-dependent effects in experimental autoimmune encephalomyelitis (EAE) development (2). This prominent role of CCR4-expressing DCs in EAE was unexpected, because DCs expressed only low levels of CCR4 compared with T-cell subsets.…”
mentioning
confidence: 98%
“…We appreciate the comments of Othy et al (1) in response to our recently published article (2). The authors treated myelin oligodendrocyte glycoprotein (MOG)-immunized mice with CC chemokine receptor 4 (CCR4) antagonists and did not observe an altered course of disease (1).…”
mentioning
confidence: 99%